Living with cyclone : study on storm surge prediction and disaster preparedness - Talukder, Jyotirmoy; Roy, Gauranga Deb.; Ahmad, Mohiuddin, 1952- (Dhaka, Bangladesh : Community Development Library, 1992)
With reference to Bangladesh.
Includes bibliographical references (p. [123]-124).
Keywords: Cyclones -- Bangladesh